IMPROVING STRATEGIC MARKETING ACTIVITIES IN SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Choriyeva Nigina Kaxramonovna (Modern American Journals, 2025)
This thesis discusses the role of marketing in a market economy, economic relations in the trade sector, the rapid development of small business and private entrepreneurship.
Keywords: Economy, relations, formation, development, entrepreneurship, business.